THE REFLECTION OF CLASSLESS SOCIETY IN GEORGE ORWELL’S ANIMAL FARM - Nur, Nurul Akbar; Arafah, Burhanuddin (JURNAL ILMU BUDAYA, 2020)
This research intends to the classless society in Animal Farm. Therefore, the researchers analyzed how the reflection of the classless society in the novel. In analyzing this research, the researchers used a sociological approach to describes the classless society that is reflected in the novel Animal Farm. The researcher analyzes literary work based on the text and explains the sociological meaning by uses Marxist literary theory. The researcher analyzes the communism concept practiced and reflected to the society (farm) to create public welfare Moreover, the researcher used a qualitative method and descriptive analysis method in analyzing the data. There are two sources of data which are primary data and supporting data. The primary data was taken of the novel Orwell’s Animal Farm. Meanwhile, the supporting data were taken from book, journal, theses, and article. The result of this research is the researchers find the author’s way to reflected the classless society in the novel.